Research on the Change of Internet Public Opinion Image of Traditional Chinese Medicine under the Background of the New Crown Epidemic: An Empirical Analysis Based on Comments of Weibo - Liu, Lirong; An, Maoxing (The Journal of Medicine, Humanity and Media, 2024)
In recent years, the popularity of traditional Chinese medicine has been constantly rising, while the comments on traditional Chinese medicine on the internet are mixed. In order to further understand the image of TCM in the mouths of netizens, this paper takes Weibo user comments as a research sample, uses Python to mine and process the Weibo text about TCM from 2017 to 2023, encodes the text according to the source, release time, publisher identity, issue, etc., and studies the current situation and changes of TCM online public opinion image under the background of the new crown epidemic through content analysis. The study found that after the epidemic, the popularity of TCM online public opinion increased significantly, except for the topic of TCM medical institutions, netizens’ attitudes towards other topics improved, and it was found that KOL bloggers had better effects than ordinary bloggers in spreading TCM. Based on the research results and the formation process of public opinion, this paper puts forward suggestions such as creating a good public opinion environment, building a TCM network communication team, subdividing communication strategies for different topics, and cultivating TCM communication opinion leaders, hoping to help improve the image of TCM online public opinion.